2017
DOI: 10.17305/bjbms.2017.2208
|View full text |Cite
|
Sign up to set email alerts
|

Oligoasthenoteratozoospermic (OAT) men display altered phospholipase C ζ (PLCζ) localization and a lower percentage of sperm cells expressing PLCζ and post-acrosomal sheath WW domain-binding protein (PAWP)

Abstract: Oligoasthenoteratozoospermia (OAT) is demonstrated to be one of the most common causes of male subfertility. Phospholipase C ζ (PLCζ), a sperm-specific protein, is considered to be one of the sperm-borne oocyte activating factors (SOAFs), which play a vital role in fertilization. The post-acrosomal sheath WW domain-binding protein (PAWP) is another candidate for SOAF. The aim of this study was to compare the PLCζ localization patterns and percentage of PLCζ- and PAWP-positive sperm cells in patients with OAT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Sperm from infertile men consistently failed to activate oocytes and could either not elicit a Ca 2+ release in mouse oocytes or did so abnormally [ 13 , 16 ]. Such sperm exhibit abrogated PLCζ [ 1 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 22 , 23 , 25 , 26 , 27 , 28 , 36 , 37 , 38 , 39 , 40 ], suggesting that PLCζ defects underlie, or at least contribute to, such cases of fertilisation failure. Clinically, complete fertilisation failure is attributed to sperm-specific defective oocyte activation, rather than any other cause [ 1 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sperm from infertile men consistently failed to activate oocytes and could either not elicit a Ca 2+ release in mouse oocytes or did so abnormally [ 13 , 16 ]. Such sperm exhibit abrogated PLCζ [ 1 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 22 , 23 , 25 , 26 , 27 , 28 , 36 , 37 , 38 , 39 , 40 ], suggesting that PLCζ defects underlie, or at least contribute to, such cases of fertilisation failure. Clinically, complete fertilisation failure is attributed to sperm-specific defective oocyte activation, rather than any other cause [ 1 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, complete fertilisation failure is attributed to sperm-specific defective oocyte activation, rather than any other cause [ 1 , 31 ]. The most rapidly applicable approach is the immunocytological analysis of sperm PLCζ [ 1 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 22 , 23 , 25 , 26 , 27 , 28 , 36 , 37 , 38 , 39 , 40 ]. However, varying protocol efficiencies have yielded conflicting outcomes between studies examining human sperm PLCζ [ 15 , 18 , 29 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that failed fertilization after ICSI in some cases of infertile men (i.e., globozoospermic, oligoasthenoteratozoospermic, normozoospermic patients) is related to reduced expression and abnormal localization of PLCζ protein (Azad et al, ; Chithiwala et al, ; Durban et al, ; Lee et al, ; Tavalaee, Nomikos, Lai, & Nasr‐Esfahani, ). Despite the key role of PLCζ in the fertilization process and its potential as biomarker for the ability of sperm to induce oocyte activation, the status of this protein in unexplained infertile (UI) and asthenoteratozoospermic (AT) men remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Disruption of PLCζ by genetic mutations or reduced protein expression has been reported in patients suffering from FF after ICSI, irrespective of the sperm quality. PLCζ deficiency has been observed in normozoospermic males [39][40][41] but also in patients with abnormal sperm parameters [42,43], with globozoospermia being the most characteristic example [9,44,45]. The current evidence undoubtedly supports the role of PLCζ as a protein indispensable for successful fertilization, but there are still some unknowns that remain to be solved [46,47].…”
Section: Introductionmentioning
confidence: 85%